Malignant melanoma showing smooth muscle differentiation. Issue 11 (November 1996) - Banerjee, S S; Bishop, P W; Nicholson, C M; Eyden, B P
Abstract : A unique case of a metastatic non-desmoplastic sarcomatoid malignant melanoma in an axillary lymph node showing smooth muscle differentiation in a 54 year old woman is described. The tumour cells exhibited alpha-smooth muscle actin, HHF-35 and desmin positivity but were negative for S100 protein and HMB-45. Ultrastructural examination revealed smooth muscle phenotype and there was no evidence of myofibroblastic differentiation, a feature described previously in desmoplastic melanomas.